Cardioprotective effect of Sanguisorba minor against isoprenaline-induced myocardial infarction in rats - Hosseini, Azar; Ghorbani, Atieh; Alavi, Mohaddeseh Sadat; Forouhi, Nima; Rajabian, Arezoo; Boroumand-Noughabi, Samaneh; Sahebkar, Amirhossein; Eid, Ali H. (Frontiers in Pharmacology, 2023)
Oxidative stress is major instigator of various cardiovascular diseases, including myocardial infarction (MI). Despite available drugs, there is still an increased need to look for alternative therapies or indentifyidentify new bioactive compounds. Sanguisorba minor (S. minor) is a traditional native herb that is characterized by a its potent antioxidant activity. This study was designed to evaluate the effect of S. minor against isoprenaline-induced MI. Rats received were treated with the hydro-ethanolic extract of the aerial parts of S. minor at the doses of 100, or 300 mg/kg orally for 9 days. Isoprenaline was injected subcutaneously at the dose of 85 mg/kg on 8 th and 9 th days 8 and 9. Then theA activities of various cardiac injury markers including cardiac troponin (cTnT), lactate dehydrogenase (LDH), creatinine kinase muscle brain (CK-MB), and creatinine phosphokinase (CPK) and antioxidant enzymes in serum were determined.Malondialdehyde (MDA) and thiol content were measured in cardiac tissue, and histopathological analysis were was conducted. Our results show that isoprenaline increased the serum levels of cTnT, LDH, CK-MB and CPK (p<0.001) and elevated MDA level (p<0.001) level in in cardiac tissue. Isoprenaline also reduced superoxide dismutase (SOD), catalase, and thiol content (p<0.001). Importantly, the extract attenuated abolished isoprenaline-induced MI by elevating of SOD and, catalase antioxidant enzymes (p<0.001), and reducing levels of MDA, level andas well as diminishing levels of cTnT, LDH, CK-MB and CPK cardiac markers (p<0.001).Histopathological studies of the heart cardiac tissue showed isoprenaline-induced cardiac injury while the extractthat was significantly attenuated by the extract reduced cardiac damage at high dose. Our results suggest that S. minor could abrogate isoprenaline-induced cardiac toxicity due to its ability to mitigate oxidative stress.